LncRNA PVT1 promotes cuproptosis through transcriptional activation of FDX1 in colorectal cancer - Jinyan Ma; Yingjie Zhang; Zhuoran Sun; Hui Guo; Xiang Li; Jueting Cai; Meichen Zhang; Mengmeng Chen; Jingjing Jiang; Lingling Zhang (Redox Biology)
Background: Cuproptosis, a copper-dependent form of regulated cell death, has emerged as a redox-sensitive vulnerability in cancer. However, the molecular basis by which this process is initiated and sustained in tumors remains poorly defined. Methods: We investigated the functional role of FDX1 in cuproptosis in colorectal cancer through a series of in vivo and in vitro assays. Differential gene expression analysis and correlation studies were employed to identify long noncoding RNAs (lncRNAs) that regulate FDX1. Techniques such as molecular docking simulations, chromatin isolation by RNA purification (ChIRP), chromatin immunoprecipitation (ChIP), luciferase reporter assays, and bioinformatics analysis have elucidated the interactions and mechanisms between PVT1 and FDX1. The therapeutic potential of the PVT1-FDX1 axis was evaluated in a mouse xenograft model. Results: FDX1 is upregulated in colorectal cancer and is indispensable for cuproptosis both in vitro and in vivo. The cuproptosis-related lncRNA PVT1 acts as a novel upstream regulator of FDX1. Mechanistically, PVT1 directly binds to the FDX1 promoter, increasing H3K27ac deposition and activating FDX1 transcription. Our findings also revealed that 35/98 nt of PVT1 bind to the −104/-41 bp region of the FDX1 promoter. Additionally, PVT1 was found to recruit SF1 to the FDX1 promoter, further enhancing FDX1 expression, leading to proteotoxic stress and ultimately triggering copper-dependent cell death. Clinically, PVT1 increases tumor sensitivity to cuproptosis by promoting FDX1 transcription. Conclusions: We identify a novel regulatory axis in which PVT1 promotes cuproptosis by epigenetically activating FDX1 in colorectal cancer. Targeting the PVT1-FDX1 axis may offer an effective anticancer strategy, particularly given the widespread overexpression of PVT1 and its role in therapy resistance.